Peningkatan Kemandirian Warga Kampung Susun Kunir melalui Panduan Perizinan UMKM - Rona Fika Jamila; Gentina Pratama Putra (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2026)
For MSMEs, legality is crucial, as it provides legal certainty and empowers them to develop their businesses. Legality for MSMEs is typically known as a Micro, Small, and Medium Enterprise Permit (IUMK). While business space in Kampung Kunir has been provided, its utilization is still suboptimal. Instead, residential areas are being used for business. However, not all MSMEs have business permits, or they are unaware of the process. The purpose of this Community Service Program is to educate MSMEs on how to obtain permits for their products, equip them with awareness and a willingness to be "literate" about the legality of their products, and improve the quality of human resources for MSMEs in this regard. The targeted output of this activity is that this guide can be created by Mercu Buana University and utilized. And if MSMEs in Kampung Kunir already have legal status, it is hoped that this will help them be more easily marketed and more easily developed in the future. The method is through socialization of activities and direct mentoring. This activity resulted in a guidebook that can be distributed to MSMEs in Kampung Kunir to help them improve the legal status of their businesses.